2021
DOI: 10.3390/cancers13246211
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αE(CD103)β7 in Epithelial Cancer

Abstract: Interactions of both the innate and the adaptive immune system with tumors are complex and often influence courses and therapeutic treatments in unanticipated ways. Based on the concept that CD8+T cells can mediate important antitumor effects, several therapies now aim to amplify their specific activity. A subpopulation of CD8+ tissue-resident T lymphocytes that express the αE(CD103)β7 integrin has raised particular interest. This receptor presumably contributes to the recruitment and retention of tumor-infilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 107 publications
(153 reference statements)
2
9
0
Order By: Relevance
“…CD103 is a subunit of the αE/β7 integrin that helps to retain expressing cells on the epithelium. 24 CD103 has been proposed as a marker of activated and tumorreactive CD8 + T cells in ascites HGSC 25,26 but no data correlated with survival was given. We showed that CD103 was mostly expressed on CD8 + , and not on CD4 + subsets, which was shown by us and by two other studies.…”
Section: Discussionmentioning
confidence: 99%
“…CD103 is a subunit of the αE/β7 integrin that helps to retain expressing cells on the epithelium. 24 CD103 has been proposed as a marker of activated and tumorreactive CD8 + T cells in ascites HGSC 25,26 but no data correlated with survival was given. We showed that CD103 was mostly expressed on CD8 + , and not on CD4 + subsets, which was shown by us and by two other studies.…”
Section: Discussionmentioning
confidence: 99%
“…CD103 (αE)β7 integrin binds to E-cadherin expressed by epithelial cells. The CD103 role is well known to allow CD103 + tissue-resident memory T cells to adhere to epithelial cells and reside in tissues [33]. In cancer, CD8 + CD103 + TIL participate in tumor cell killing and cytokine production within the TME [34].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, E-cadherin found in epithelial cells also interacts with some surface markers found on some subsets of T cells to modulate the immune system [71]. E-cadherin has been shown to interact with CD103 found on cytotoxic T lymphocytes (CTLs) and tissue-resident T lymphocytes (TREMs), activating the cytotoxic functions of these cells in a TCR-dependent manner [72,73]. E-cadherin also interacts with killer cell lectin-like receptor G1 (KLRG1) on the surface of NK and CD8+ cells, inhibiting TCR signaling and thus the effector functions of these cells [74][75][76].…”
Section: E-cadherin In Acute Leukemiamentioning
confidence: 99%